2024
DOI: 10.1186/s12877-023-04651-1
|View full text |Cite
|
Sign up to set email alerts
|

Does digital technology make people healthier: the impact of digital use on the lifestyle of Chinese older adults

Kaichang Cui,
Wei Zou,
Xiang Ji
et al.

Abstract: Background With the arrival of the era of large-scale production, sharing and application of data, digital use has gradually changed people’s daily entertainment, consumption, social interaction, learning and other behaviors in its efficient form. This paper mainly discusses whether this fast and convenient behavior leads Chinese older adults to adopt healthier lifestyles. Methods Using the most recent information from the Chinese Family Panel Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…At the same time, Internet use can also improve the health of older adults by increasing their likelihood of exercise [ 9 ]. Cui et al [ 10 ] found that the frequency of digital use significantly improves the diet, sleep, exercise, smoking, and alcohol consumption of Chinese older adults. Digital technology can promote healthy lifestyles in various ways, thereby improving the health status of Chinese older adults.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, Internet use can also improve the health of older adults by increasing their likelihood of exercise [ 9 ]. Cui et al [ 10 ] found that the frequency of digital use significantly improves the diet, sleep, exercise, smoking, and alcohol consumption of Chinese older adults. Digital technology can promote healthy lifestyles in various ways, thereby improving the health status of Chinese older adults.…”
Section: Literature Reviewmentioning
confidence: 99%